Simple Screening for High-Risk Pregnancies in Rural Areas Based on an Expert System - Retno Supriyanti; Ahmad Fariz; Teddy Septiana; Eko Murdyantoro; Yogi Ramadhani; Haris Budi Widodo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
The high maternal and infant mortality rates in developing countries, especially Indonesia, are quite alarming. There are many factors that cause high mortality numbers; one of them is the delay in handling cases of high‑risk pregnancies. The main problem faced by developing countries is the lack of health facilities, including medical equipment and human resources. This research aims to develop a simple system that can be used to screen high‑risk pregnancies. This system is based on an expert system. The Analytical Hierarchy Process (AHP) method is used in making decisions about potentially high-risk pregnancy patients. Essentially, the system can be used by anyone, anywhere, to carry out early screening of high‑risk pregnancy patients, so that delays in the treatment of these patients can be resolved, because the symptoms of high‑risk pregnancy are known from the beginning. Results indicate that this system shows promise for further development.